Ungleiche Versorgung von Flüchtlingskindern: Implikationen für eine Ethik in Behörden = Unequal care for refugee children: implications for ethics in public authorities - Zimmer, Matthias (Zeitschrift für medizinische Ethik, 2025)
AbstractIn the care of refugee children from Ukraine, inconsistencies in the decisions made by the authorities regarding their medical care and access to the education system have been identified. This article examines the responsibility of the public administration for its actions from a legal, social, political and moral perspective. This leads to the need for a structured introduction of administrative ethics into the daily work of the authorities, which has a direct impact on medical practice., AbstractIn the care of refugee children from Ukraine, inconsistencies in the decisions made by the authorities regarding their medical care and access to the education system have been identified. This article examines the responsibility of the public administration for its actions from a legal, social, political and moral perspective. This leads to the need for a structured introduction of administrative ethics into the daily work of the authorities, which has a direct impact on medical practice.